Diffusion of integrated reporting in an emerging South Asian (SAARC) nation. Issue 4 (4th April 2017) - Gunarathne, Nuwan; Senaratne, Samanthi
Abstract : Purpose: This paper aims to examine how and why integrated reporting (IR) as a managerial technology is diffused in Sri Lanka, an emerging South Asian (South Asian Association for Regional Cooperation) nation, from an expansion diffusion perspective. Design/methodology/approach: The study followed two analytical steps. First, the adopter groups of IR of the country's stock exchange were identified based on their annual reports. Second, the key stakeholders (both internal and external) in the process of IR diffusion in the country were interviewed. Thereafter, a content analysis of these semi-structured interviews was carried out based on the demand-pull and supply-push sides of the diffusion theory of innovation. Findings: The temporal trend of IR suggests that the country is currently in the diffusion stage with many first time adopters are likely to join the bandwagon of IR. In the primary stage, its early adoption has been driven by the efficient-choice perspective. However, in the diffusion stage, most of the adopters are driven by fashion setting, which is mainly attributable to the active propagators in the supply side of IR diffusion. IR has been mainly a transition evolving through the incremental changes in sustainability reporting. Many firms have not internalized the IR principles with the danger of IR becoming a mere reporting mechanism. Originality/value: The application of both demand-pull and supply-push sides of the diffusion theory of innovation is still limited, particularly in the case of new reporting mechanisms. The study provides new insights into how these two forces contribute to creating a "practice-reporting portrayal gap" in IR.